Answer:
The fourth one Its tell you to add or miners or multiple
Step-by-step explanation:
And then the rest is telling you to explain you answer using your own words.
<h2>Answer:</h2><h3>W = 5</h3><h3>Step-by-step explanation:</h3><h3>Simplify the brackets. </h3><h3>-2x^2 + wx - 4 - x^2 - 5x - 6 = -3x^2 - 10</h3><h3>Then simplify (-2x^2 + wx - 4 - x^2 - 5x - 6) to </h3><h3>( -3x^2 + wx - 10 - 5x)</h3><h3>This will give you 3x^2 + wx - 10 - 5x = -3x^2 - 10. </h3><h3>Now you need to cancel out -3x^2 on both sides. </h3><h3>wx - 10 - 5x = -10</h3><h3>Then cancel out -10 from both sides. </h3><h3>wx - 5x = 0</h3><h3>Now factor out the common term. (x) </h3><h3>w - 5 = 0.</h3><h3>giving you the answer w = 5. </h3><h3 /><h3 /><h3>welcome. *yeets*</h3>
Answer:
B
Step-by-step explanation:
its b solve the first equation for y \
hope this helps
brainliest would be appreciated
Answer:
The inverse is ±sqrt(100-x)
Step-by-step explanation:
To find the inverse, exchange x and y
x = 100 -y^2
Solve for y
Subtract 100 from each side
x - 100 = -y^2
Divide by -1
-x +100 = y^2
Take the square root of each side
±sqrt(100-x) = sqrt(y^2)
±sqrt(100-x) =y
The inverse is ±sqrt(100-x)